Multi-omics in Spinal Cord Injury: Diagnosis, Prognosis, and Treatment: Multi-omics in Spinal Cord Injury - Xu, Hanxun; Zhao, Wenhai; Zhou, Yimin; Zhang, Li (Cellular and Molecular Biology, 2022)
A spinal cord injury (SCI) can result in varying degrees of limb movement impairment and sensory impairment, affecting the quality of life severely. The study of the molecular mechanisms underlying SCI disease has advanced greatly. However, there is still room for improvement in terms of the cognitive and systematic approaches used for disease diagnosis, progression, treatment, and prognosis. This situation might change as multi-omics technology advances. Single omics technology has some limitations when it comes to fully comprehending the disease progression pattern and directing SCI treatment. Therefore, a thorough understanding of the state of the art in omics research on SCI can explain the pathogenesis and mechanism of the disease and offer new, multifaceted treatments for SCI. This article reviews recent developments in the application of various omics techniques to diseases associated with SCI and discusses the advantages and disadvantages of using these techniques for disease diagnosis, prognosis, and treatment.